Design of a rectifier for 2.45 GHz wireless power transmission - Defu Wang; Renato Negra (PRIME 2012; 8th Conference on Ph. D. Research in Microelectronics & Electronics, 2012)
This paper presents a high-efficiency rectifying circuit for wireless power transmission at 2.45 GHz. A filtering and matching network designed by quarter wavelength stubs was developed for suppressing the second and the third order harmonics of 2.45 GHz, 4.9 GHz and 7.35 GHz, respectively. The measured RF-to-DC conversion efficiency is 66.5 % for an input power level of 10 mW.